ANALYSIS OF VISUAL ATTENTION AMONG SMOKER AND NON-SMOKER BY USING HUMAN EYE TRACKER OF HEALTH GRAPHIC WARNING ON TOBACCO PACKAGE - Rizki Edmi Edison; Yayu Hizza Anisa; Fikry Ravi Fauzy (Faculty of Public Health, Andalas University, 2021)
The placement of Health Graphic Warning on tobacco package has been implementing in Indonesia for years. However, the number of smokers in Indonesia is not decreased. Many studies based on interview about perception of Health Graphic Warning gave difference results. This study analysed the visual attention of smokers while looking at tobacco package and compared with non-smoker by using human eye tracker. 50 persons (25 smoker and 25 non-smokers) of 18 – 20 years old adolescents were participated in this study. Image of tobacco package that contained health graphic warning was shown to participants through monitor alternate with neutral image. It revealed that smokers and non-smokers have different pattern where non-smokers will focus to smoking-related disease and smoker will focus to logo of tobacco.